Blood-brain barrier disruption measured by albumin index correlates with inflammatory fluid biomarkers. Issue 5 (May 2023) - Hillmer, Laura; Erhardt, Erik B; Caprihan, Arvind; Adair, John C; Knoefel, Janice E; Prestopnik, Jill; Thompson, Jeffrey; Hobson, Sasha; Rosenberg, Gary A
Blood-brain barrier (BBB) permeability can be measured by the ratio of albumin in cerebrospinal fluid (CSF) and blood and by dynamic contrast-enhanced MRI (DCEMRI). Albumin is a large molecule measured in CSF and blood to form the albumin index (Qalb ), which is a global measure of BBB permeability, while the smaller Gadolinium molecule measures regional transfer (Ktrans ); few studies have directly compared them in the same patients. We used both methods as part of a study of mechanisms of white matter injury in patients with different forms of dementia. In addition, we also measured biomarkers for inflammation, including proteases, angiogenic growth factors, and cytokines, and correlated them with the BBB results. We found that there was no correlation between Qalb and Ktrans . The Qalb was associated with the matrix metalloproteinases (MMP-2, MMP-3, and MMP-10), the angiogenic factors (VEGF-C and PlGF), and the cytokines (IL-6, IL-8 and TNF-α). On the other hand, Ktrans was associated with the diffusion measures, mean free water and PSMD, which indicate white matter injury. Our results show that the Qalb and Ktrans measure different aspects of BBB permeability, with albumin being a measure of inflammatory BBB opening and Ktrans indicating white matter injury.